Circulating metabolites modulated by diet are associated with depression. - van der Spek, Ashley; Stewart, Isobel D; Kühnel, Brigitte; Pietzner, Maik; Alshehri, Tahani; Gauß, Friederike; Hysi, Pirro G; MahmoudianDehkordi, Siamak; Heinken, Almut; Luik, Annemarie I; Ladwig, Karl-Heinz; Kastenmüller, Gabi; et al. (Springer Science and Business Media LLC, 2023)
Metabolome reflects the interplay of genome and exposome at molecular level and thus can provide deep insights into the pathogenesis of a complex disease like major depression. To identify metabolites associated with depression we performed a metabolome-wide association analysis in 13,596 participants from five European population-based cohorts characterized for depression, and circulating metabolites using ultra high-performance liquid chromatography/tandem accurate mass spectrometry (UHPLC/MS/MS) based Metabolon platform. We tested 806 metabolites covering a wide range of biochemical processes including those involved in lipid, amino-acid, energy, carbohydrate, xenobiotic and vitamin metabolism for their association with depression. In a conservative model adjusting for life style factors and cardiovascular and antidepressant medication use we identified 8 metabolites, including 6 novel, significantly associated with depression. In individuals with depression, increased levels of retinol (vitamin A), 1-palmitoyl-2-palmitoleoyl-GPC (16:0/16:1) (lecithin) and mannitol/sorbitol and lower levels of hippurate, 4-hydroxycoumarin, 2-aminooctanoate (alpha-aminocaprylic acid), 10-undecenoate (11:1n1) (undecylenic acid), 1-linoleoyl-GPA (18:2) (lysophosphatidic acid; LPA 18:2) are observed. These metabolites are either directly food derived or are products of host and gut microbial metabolism of food-derived products. Our Mendelian randomization analysis suggests that low hippurate levels may be in the causal pathway leading towards depression. Our findings highlight putative actionable targets for depression prevention that are easily modifiable through diet interventions.
Keywords: 3205 Medical Biochemistry and Metabolomics; 32 Biomedical and Clinical Sciences; Clinical Research; Prevention; Depression; Mental Health; Nutrition; Mental health